2021
DOI: 10.1111/jfpp.15196
|View full text |Cite
|
Sign up to set email alerts
|

Whey protein isolate‐based films incorporated with nanoemulsions of orange peel ( Citrus sinensis ) essential oil: Preparation and characterization

Abstract: The aim of the present study was to prepare whey protein isolate (WPI)‐based films containing Citrus sinensis peel essential oil (CSEO) loaded emulsions and nanoemulsions (2.5% and 5% of WPI), as an active packaging system. The fabricated films were characterized by Fourier transform infrared spectroscopy, Filed Emission Scanning Electron Microscopy, X‐ray diffraction, and tensile analyses. The obtained results approved the appropriate interactions between WPI matrix and CSEO emulsion and nanoemulsion due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Results presented in Table 1 show that the luminosity of both T and S nanoemulsions are significantly lower than those of the control emulsions; b* value for T nanoemulsion is significantly higher than that of the T Control emulsion which indicates a more pronounced yellow tone for T nanoemulsion. Similar changes related to the addition of EOs and/or T to emulsions and to the sonication step were reported by other research groups [ 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 84%
“…Results presented in Table 1 show that the luminosity of both T and S nanoemulsions are significantly lower than those of the control emulsions; b* value for T nanoemulsion is significantly higher than that of the T Control emulsion which indicates a more pronounced yellow tone for T nanoemulsion. Similar changes related to the addition of EOs and/or T to emulsions and to the sonication step were reported by other research groups [ 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 84%
“…The incorporation of nanofiller such as whey protein–corn oil-TiO 2 NPs [ 50 ] and whey protein–chitosan nanofiber–nano-formulated cinnamon oil [ 163 ] has also been examined. Finally, the incorporation of active agents such as whey protein–nanoemulsions of orange peel ( Citrus sinensis ) essential oil has been studied [ 51 ].…”
Section: Biodegradable Polymers Currently Used In the Food Packaging ...mentioning
confidence: 99%
“…These authors observed that when applied to ground meat, the antimicrobial efficiency of the microemulsion-films was much higher than that of the control films against coliforms, Staphylococcus aureus , yeast, mold, and lactic acid bacteria. On another side, Amjadi et al 121 produced films based on whey protein isolated incorporated with emulsified orange peel ( Citrus sinensis ) essential oil and observed that the antioxidant and antimicrobial activities of the active films loaded with nanoemulsions were significantly higher than those of films loaded with an emulsion.…”
Section: Application Of Active Films Incorporated With Emulsions-base...mentioning
confidence: 99%